Dancing in the wings - Allen, Debbie; Nelson, Kadir (New York : Puffin Books, 2003)
Sassy tries out for a summer dance festival in Washington, D.C., despite the other girls' taunts that she is much too tall.
First published in the U.S.A.: Dial Books for Young Readers, 2000.
2.8
K-3
Keywords: Ballet -- Fiction; Dance festivals -- Fiction; Self-confidence -- Fiction; Teasing -- Fiction; Washington (D.C.) -- Fiction; Ballet -- Fiction; Dance festivals -- Fiction; Self-confidence -- Fiction; Teasing -- Fiction; Washington (D.C.) -- Fiction